TANGGAPAN MAHASISWA TERHADAP QUIZLET SEBAGAI MEDIA PEMBELAJARAN KANJI - Triandani, Eca; Basri, Merri Silvia; Yohani, Adisthi Martha (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: Learning a foreign language is not an easy task to do including Japanese language. Kanji as one of the letters in Japanese find difficult to learn by the Japanese language learners. The difficulties include the memorizing, writing, and so forth. To facilitate the learning process, a learning media is needed in supporting the better understanding of the learners. This study explores a media called Quizlet and its purpose is exploring students’ responses toward Quizlet as a media to learn Kanji. This study use descriptive quantitative method with 32 students batch 2019 from Japanese Language Education Department in Universitas Riau as the respondents and the data is collected through a close-ended questionnaire. The result found that 48% students agree and 38% students strongly agree which show that the students approve the use of Quizlet as a media to learn Kanji. Therefore, Quizlet can be used as the learning media for Kanji in the future since it facilitates the students in their learning process of KanjiKey Words: Response, Quizlet, Kanji, Learning media